2012
DOI: 10.1088/0953-4075/45/21/215001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the electromagnetically induced transparency in the era of cosmological hydrogen recombination

Abstract: Investigation of the cosmic microwave background formation processes is one of the most actual problem at present time. In this paper we analyze the response of the hydrogen atom to the external photon fields. Field characteristics are defined via conditions corresponding to the recombination era of universe. Approximation of three-level atom is used to describe the "atom -fields" interaction. It is found that the phenomena of the electromagnetically induced transparancy (EIT) takes place in this case. Conside… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Recently, the density matrix formalism was applied to study the effect of Electromagnetically-Induced Transparency (EIT) in hydrogen atom under the conditions corresponding to the recombination era of the universe [7,8]. It was shown that the EIT phenomenon could lead to corrections on the order of 1% in the observed cosmic microwave background (CMB).…”
Section: Correction To the Optical Depth Via The Evaluation Of Three-mentioning
confidence: 99%
“…Recently, the density matrix formalism was applied to study the effect of Electromagnetically-Induced Transparency (EIT) in hydrogen atom under the conditions corresponding to the recombination era of the universe [7,8]. It was shown that the EIT phenomenon could lead to corrections on the order of 1% in the observed cosmic microwave background (CMB).…”
Section: Correction To the Optical Depth Via The Evaluation Of Three-mentioning
confidence: 99%
“…Velocity selection arises because the sensitivity to Doppler shift is weak (LTE principle), Doppler reduction of frequency for the one of photons is compensated by the corresponding increase of frequency for other one. Recently, it was shown also that the EIT phenomenon should be taken into account by means of upgrade of the Sobolev escape probability [6]. In accordance to [4], the Sobolev optical depth should be defined in terms of the Einstein coefficients.…”
Section: Theory and Basic Equationsmentioning
confidence: 99%
“…Recently the cascade 1s − 2p − 3s scheme for the hydrogen atom was considered [6]. It was shown that in the case of exact resonances (when both detunings ∆ p and ∆ c are equal to zero) the maximal value of the f , Eqs.…”
Section: Ladder or Cascade Scheme ξmentioning
confidence: 99%
See 2 more Smart Citations